The Experience of Medical Students in UIN Malang When Studying CSL During The COVID 19 Pandemic - Riskiyah, Riskiyah (Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
Covid-19 is a pandemic that is occurring in various countries. Covid-19 severely impacts all sectors, especially education. The Indonesian government has imposed social distractions so that, for the time being, the learning process must be done online. UIN Malang Medical Education Study Program in Pandemic also applies the rules that all teaching and learning processes must be carried out at home, including lecture activities and CSL (Clinical Skills Laboratory). In CSL activities, students learn related clinical skills using various tools in the CSL laboratory, but when they have to study at home. The CSL learning process in medical education is critical and needs attention. This study aimed to determine students' experiences of the UIN Malang Medical Education Study Program when learning CSL during the COVID-19 pandemic. This research method is phenomenology qualitative research. This research was conducted at the Faculty of Medicine and Health Sciences UIN Malang in August 2021. Eight informants for this study represented each class of 2017, 2018, 2019, and 2020. The results of this study found seven themes, namely CSL learning videos help students to learn, delivery of material by instructors when guided, instructors practicing skills taught while trained, signal difficulties during CSL learning, students having difficulty finding alternative tools and making videos for response activities, providing feedback by instructors to students during the response, students skills are lacking in online learning. This study concludes that many students experience difficulties during the online CSL learning process, both in terms of signals and tools and in making responsive videos, and the skills students lack.